USO DO ÓLEO ESSENCIAL DE GENGIBRE (ZINGIBER OFFICINALE) NA ÁGUA DE TRANSPORTE DE LAMBARI (ASTYANAX LACUSTRIS) - CAVALCANTI, Leandro Borges; CAITANO, Welison Aparecido Bispo; COSTA, Deliane Cristina; CAMPOS, Cristiane Meldau; WANDERLEY, Alysson Martins; FERREIRA, Andre Lima (ANAIS DO ENIC, 2025)
-